Managing low sexual desire in women. (September 2011) - Maclaran, Kate; Panay, Nick
Low sexual desire is a prevalent symptom, but not one frequently volunteered by women. When accompanied by distress, loss of libido is known as hypoactive sexual desire disorder, which can have a significant impact on a woman's wellbeing. The etiology of hypoactive sexual desire disorder is multifactorial and its management requires a combination of psychosocial and pharmacological interventions. This article outlines the assessment of patients presenting with the symptom of low sexual desire and discusses the evidence for pharmacological management.